Beyond Bullying. (November 2014) - Fields, Jessica; Mamo, Laura; Gilbert, Jen; Lesko, Nancy
Sociologists Jessica Fields and Laura Mamo, along with education researchers, Jen Gilbert and Nancy Lesko, report on their high school storytelling project, Beyond Bullying, that invited teachers, students and community members to record stories of LGBTQ sexuality that moved beyond tales of depression, bullying and suicide towards ordinary narratives of love, loss, friendship and family.